The AI advantage : how to put the artificial intelligence revolution to work - Davenport, Thomas H., 1954- (Cambridge, Massachusetts : The MIT Press, 2018)
Thomas Davenport offers a guide to using artificial intelligence in business. He describes what technologies are available and how companies can use them for business benefits and competitive advantage. He cuts through the hype of the AI craze - remember when it seemed plausible that IBM's Watson could cure cancer? - to explain how businesses can put artificial intelligence to work now, in the real world. His key recommendation: don't go for the "moonshot" (curing cancer, or synthesizing all investment knowledge); look for the "low-hanging fruit" to make your company more efficient.0Davenport explains that the business value AI offers is solid rather than sexy or splashy. AI will improve products and processes and make decisions better informed-important but largely invisible tasks. AI technologies won't replace human workers but augment their capabilities, with smart machines to work alongside smart people. AI can automate structured and repetitive work; provide extensive analysis of data through machine learning ("analytics on steroids"), and engage with customers and employees via chatbots and intelligent agents. Companies should experiment with these technologies and develop their own expertise. Davenport describes the major AI technologies and explains how they are being used, reports on the AI work done by large commercial enterprises like Amazon and Google, and outlines strategies and steps to becoming a cognitive corporation.
OCLC-licensed vendor bibliographic record.
Keywords: elektronické knihy; electronic books; Artificial intelligence -- Economic aspects; Artificial intelligence -- Industrial applications; Technological innovations -- Economic aspects; BUSINESS/Business Technology; BUSINESS/Management